The Impact Of Transformational Leadership On Organizational Performance And Employee Motivation - Suryadi, Yadi; Dewi, Ni Luh Yulyana; Trisnawati, Trisnawati; Al-Amin, Al-Amin (Transforma Jurnal Manajemen, 2024)
Transformational leadership is a leadership approach that focuses on inspiring and motivating employees to achieve higher performance and achieve organizational goals. Descriptive qualitative methods were used to understand the impact of transformational leadership on organizational performance and employee motivation through in-depth interviews, observations and document analysis. This research found that transformational leaders tend to have a clear vision and are able to communicate this vision effectively to employees, so that employees feel inspired and motivated to work better. In addition, transformational leaders also provide emotional and intellectual support to employees, helping them in personal and professional development. This creates a positive and collaborative work environment, which in turn improves overall organizational performance. From the interviews, employees stated that they felt more appreciated and motivated to contribute to the success of the organization when led by a transformational leader. Employees' intrinsic motivation increases because they feel they have an important role in achieving the organization's vision and mission. In addition, transformational leaders also encourage innovation and creativity, which are important factors in improving organizational performance. Overall, transformational leadership has a significant positive impact on organizational performance and employee motivation. Leaders who are able to inspire and motivate employees effectively can create a dynamic and productive organizational culture. Thus, the application of transformational leadership in various types of organizations can be an effective strategy for achieving competitive advantage and sustainable growth.